Puncture-resistant starch-based biodegradable PBAT (poly (butylene adipate-co-terephthalate)) film and preparation method thereof

By modifying starch with nadic anhydride glyceride and combining PBAT resin and PLA resin, a puncture-resistant starch-based biodegradable PBAT film was prepared, which solved the problem of degradation of the puncture resistance of the film after starch filling modification, and achieved Performance improvement and application scope expansion.

CN119463431AActive Publication Date: 2025-02-18WANHUA CHEMICAL (NINGBO) CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411774925.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

When modified with starch filling, the puncture resistance of PBAT films is reduced and they are easily penetrated and cracked by sharp objects, limiting their use in biodegradable materials.

Method used

Nadic acid anhydride glyceride is obtained by reacting nadic acid anhydride and glycerol, and the starch is modified. Combined with PBAT resin, PLA resin and modified starch, a puncture-resistant starch is prepared.

Benefits of technology

It improves the puncture resistance and mechanical strength of starch-based biodegradable PBAT film, and expands its application range in biodegradable materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171171890000041
    Figure BDA0005171171890000041
  • Figure BDA0005171171890000081
    Figure BDA0005171171890000081
Patent Text Reader

Abstract

The invention discloses a puncture-resistant starch-based biodegradable PBAT film and a preparation method, and relates to the technical field of biodegradable plastics, the PBAT film is mainly prepared from the following components: PBAT (poly (adipic acid-butylene terephthalate)) resin, PLA (polylactic acid) resin, modified starch, a plasticizer and a lubricant; the modified starch is prepared by modifying common starch with nadic anhydride glyceride. The nadic anhydride glyceride can improve the hydrophobicity and the mechanical property of the starch, so that the puncture resistance of the starch-based biodegradable PBAT is improved, and the application range of the starch-based biodegradable PBAT in the aspects of shopping bags and packaging bags is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of degradable plastics, and in particular relates to a puncture-resistant starch-based biodegradable PBAT film and a preparation method thereof. Background Art

[0002] Traditional plastic packaging materials are usually made of polypropylene (PP) and polyethylene (PE), which are difficult to recycle after use. Disposable tableware, disposable plastic products and agricultural mulch are difficult to recycle. Their disposal methods are usually mainly incineration and landfill, causing serious environmental pollution problems. With the increase of people's environmental awareness, environmentally friendly polymer materials have received widespread attention from academia and industry. Among them, fully biodegradable plastics can be degraded in the natural environment and finally become CO2 and organic matter, thereby reducing pollution to the environment and reducing the impact of plastic waste on the ecosystem.

[0003] PBAT is a thermoplastic biodegradable plastic, a copolymer of butylene adipate and butylene terephthalate. It is a fully biodegradable polyester material that has the properties of both PBA and PBT. It has good ductility and elongation at break, as well as good heat resistance and impact resistance. It also has a certain strength after film formation. It is a very popular biodegradable material in biodegradable plastic research and one of the best biodegradable materials in the market.

[0004] However, compared with traditional plastics, PBAT has no advantages in raw materials and processing costs. Therefore, cost reduction research is an important factor in expanding its application range. Starch is rich in resources, renewable, pollution-free and has excellent biodegradability. It is increasingly favored by material scientists. However, when PBAT is filled and modified with starch, the puncture resistance of the film is significantly reduced, and it is easy to be penetrated and cracked by sharp objects. This limits its use in biodegradable materials to a certain extent. Therefore, improving its puncture resistance can effectively expand its application range. Summary of the invention

[0005] The purpose of the present invention is to provide a puncture-resistant starch-based biodegradable PBAT film and a preparation method thereof in view of the problems of the prior art.

[0006] In order to achieve the above invention object, the present invention is implemented by the following technical solutions:

[0007] A puncture-resistant starch-based biodegradable PBAT film is prepared from the following components in percentage by weight:

[0008] PBAT resin 50-80%, preferably 55-75%, such as 60%, 65%, 70%, etc.;

[0009] PLA resin 5%-20%, preferably 5-15%, such as 8%, 10%, 12%, etc.;

[0010] Modified starch 10%-30%, preferably 15-30%, such as 20%, 25%, 28%, etc.;

[0011] Plasticizer 0%-2%, preferably 0.02%-1%, such as 0.05%, 0.3%, 0.5%, etc.;

[0012] Lubricant 0%-2%, preferably 0.02%-1%, for example 0.05%, 0.3%, 0.5%, etc.

[0013] Furthermore, the PBAT resin is a low melt index resin, preferably having a melt index of 3-5 g / 10 min at 190° C. and 2.16 kg.

[0014] Furthermore, the PLA resin preferably has a melt index of 4-10 g / 10 min at 190° C. and 2.16 kg.

[0015] Furthermore, the modified starch is prepared by modifying ordinary starch with nadic anhydride glyceride, and the preparation method comprises the following steps:

[0016] (1) adding nadic anhydride, glycerol, and tetrabutyl titanate into a reaction kettle, slowly raising the temperature, introducing nitrogen gas at the same time, stirring and reacting under normal pressure until the reaction system stops producing water, and then stopping the reaction, cooling to room temperature in a nitrogen atmosphere to obtain a nadic anhydride glyceride solution;

[0017] (2) The starch and the nadic anhydride glyceride solution are uniformly mixed, an acidic compound is added, the mixture is heated for reaction, and the mixture is washed with water and then cooled and dried to obtain the nadic anhydride glyceride modified starch.

[0018] Further, in step (1), the temperature of the reaction is 170-210°C, and the reaction time is 1-4h;

[0019] Further, in step (1), the amount of glycerol added is 80%-130% by weight of the nadic anhydride, preferably 100%-120%;

[0020] The addition amount of tetrabutyl titanate is 0.1%-2% by weight of nadic anhydride, preferably 0.2%-1.0%;

[0021] Furthermore, in step (2), the starch is a combination of one or more of corn starch, potato starch, and sweet potato starch.

[0022] Further, in step (2), the amount of nadic anhydride glyceride solution added is 2%-15% by weight of the starch, preferably 2%-10%;

[0023] The acidic compound is a combination of one or more of hydrochloric acid, carbonic acid, peracetic acid, and ammonium sulfate, preferably a combination of one or more of hydrochloric acid, carbonic acid, and peracetic acid;

[0024] Furthermore, in step (2), the amount of the acidic compound added is 1%-6%, preferably 2%-5%, of the total weight of the starch and nadic anhydride glyceride solution;

[0025] Furthermore, in step (2), the reaction temperature is 30-80°C, preferably 45-75°C, and the reaction time is 2-6h, preferably 3-5h.

[0026] In the starch-based biodegradable PBAT film of the present invention, the plasticizer is one or more of tetrabutyl titanate, acetylated tributyl citrate, diisooctyl phthalate and dibutyl phthalate.

[0027] In the starch-based biodegradable PBAT film of the present invention, the lubricant is one or more of erucamide, oleamide and zinc stearate.

[0028] The method for preparing the starch-based biodegradable PBAT film of the present invention comprises the following steps:

[0029] PBAT resin, PLA resin, modified starch, optional plasticizer, and optional lubricant are uniformly mixed to obtain a mixed material; the mixed material is then melt-extruded through a twin-screw extruder, the barrel temperature of the twin-screw extruder is 50-160° C., preferably 60-150° C., and cooled and granulated to obtain a starch-based biodegradable PBAT modified material; the PBAT modified material is added to a single-screw film blowing machine for film blowing to obtain a modified PBAT film, the temperature of the single-screw film blowing machine is 100-160° C., preferably 120-150° C.

[0030] The puncture-resistant starch-based biodegradable PBAT film and preparation method provided by the present invention are characterized in that nadic anhydride and glycerol are reacted to obtain nadic anhydride glyceride, which contains unsaturated double bonds and a cyclic structure, so that the product has a specific plasticizing function and has improved extraction resistance and migration resistance to a certain extent. The starch is modified by using nadic anhydride glyceride to give the starch a certain deformability and mechanical strength, thereby improving the puncture resistance of the starch-based biodegradable PBAT.

[0031] The starch-based biodegradable PBAT film prepared by the present invention can be used to prepare shopping bags, packaging bags, etc.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1) By introducing nadic anhydride glyceride to modify starch, starch is given a certain degree of deformability and mechanical strength, which can effectively improve the puncture resistance of starch-based biodegradable PBAT;

[0034] 2) Compared with the traditional method of physical modification, the present invention uses a chemical method to modify starch. Nadic anhydride glyceride can not only react with starch, but also act as a plasticizer to improve the deformation ability of starch, thereby improving the macroscopic mechanical properties of the material. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0037] Main raw material sources

[0038] The raw material information used in the examples and comparative examples is shown in Table 1:

[0039] Table 1 Raw material information

[0040]

[0041] Other raw materials and reagents were purchased from commercial sources unless otherwise specified.

[0042] Main test methods

[0043] The test parameters and methods in the embodiments and comparative examples are shown in Table 2 below:

[0044] Table 2 Test item information

[0045] Test items unit Test Method Tensile Strength MPa GB / T 1040.3 Elongation at break % GB / T 1040.3 Puncture force N GB / T 37841

[0046] The processing equipment used is as follows:

[0047] Twin-screw extruder: Coperion ZSK 26Mc, aspect ratio 52, screw diameter 26 cm;

[0048] Film blowing machine: Lianjiang SCM25, aspect ratio 30, screw diameter 25cm;

[0049] The test equipment used is as follows:

[0050] Single-column universal testing machine: Zwick Z0.5, test standard: GB / T1040.3, GB / T37841.

[0051] Example

[0052] Embodiment 1:

[0053] (1) Preparation of Nadic Anhydride Glyceride Solution: Accurately weigh 100 g of Nadic Anhydride, 100 g of glycerol, and 0.5 g of tetrabutyl titanate, add them into a reaction kettle in sequence, slowly heat to 180° C., introduce nitrogen gas at the same time, stir and react for 2 h under normal pressure, and cool to room temperature to obtain a Nadic Anhydride Glyceride Solution;

[0054] (2) Preparation of modified starch: 1000 g corn starch was weighed and placed in a blender, 100 g nadic anhydride glyceride solution was slowly added, 30 g peracetic acid was added and heated at 60° C. with stirring for 4 h, then cooled to room temperature and kept for 30 min, washed with water, filtered and freeze-dried to obtain modified starch;

[0055] (3) Preparation of PBAT alloy: The components of PBAT alloy are: 74.4% PBAT resin, 10% PLA resin, 15% modified starch, 0.3% acetylated tributyl citrate, and 0.3% erucic acid amide. First, place PBAT and PLA resin in an oven at 90°C for 4 hours for drying. Add the above components to a high-speed mixer and mix at 600rpm / min for 5 minutes, then add them to a twin-screw extruder for extrusion. The extruder barrel temperature is 150°C. The extruded material is cooled in the extruder water tank and pelletized to obtain the PBAT alloy;

[0056] (4) Preparation of PBAT film: The prepared PBAT alloy was added into a single screw extruder for extrusion blown film at an extrusion temperature of 150° C. to obtain a PBAT film.

[0057] Embodiment 2:

[0058] (1) Preparation of Nadic anhydride glyceride solution: accurately weigh 100 g of Nadic anhydride, 105 g of glycerol, and 0.4 g of tetrabutyl titanate, add them into a reaction kettle in sequence, slowly heat to 170° C., introduce nitrogen gas at the same time, stir and react for 2 h under normal pressure, and cool to room temperature to obtain a Nadic anhydride glyceride solution;

[0059] (2) Preparation of modified starch: 1000 g corn starch was weighed and placed in a blender, 75 g nadic anhydride glyceride solution was slowly added, 35 g ammonium sulfate was added and stirred and heated at 55° C. for 4 h, then cooled to room temperature and maintained for 30 min, washed with water, filtered and freeze-dried to obtain modified starch;

[0060] (3) Preparation of PBAT alloy: The components of PBAT alloy are: 69.4% PBAT resin, 15% PLA resin, 15% modified starch, 0.3% diethyl phthalate, and 0.3% zinc stearate. First, place PBAT and PLA resin in an oven at 90°C for 4 hours for drying. Add the above components to a high-speed mixer and mix at 600rpm / min for 5 minutes, then add them to a twin-screw extruder for extrusion. The extruder barrel temperature is 155°C. The extruded material is cooled in the extruder water tank and pelletized to obtain the PBAT alloy;

[0061] (4) Preparation of PBAT film: The prepared PBAT alloy was added into a single screw extruder for extrusion blown film at an extrusion temperature of 155° C. to obtain a PBAT film.

[0062] Embodiment 3:

[0063] (1) Preparation of nadic anhydride glyceride solution: accurately weigh 100 g of nadic anhydride, 110 g of glycerol, and 0.35 g of tetrabutyl titanate, add them into a reaction kettle in sequence, slowly heat to 175° C., introduce nitrogen gas at the same time, stir and react for 2 h under normal pressure, and cool to room temperature to obtain a nadic anhydride glyceride solution;

[0064] (2) Preparation of modified starch: 1000 g corn starch was weighed and placed in a blender, 45 g nadic anhydride glyceride solution was slowly added, 35 g peracetic acid was added and heated at 50° C. with stirring for 4 h, then cooled to room temperature and kept for 30 min, washed with water, filtered and freeze-dried to obtain modified starch;

[0065] (3) Preparation of PBAT alloy: The components of PBAT alloy are: 69.4% PBAT resin, 10% PLA resin, 20% modified starch, 0.2% diethyl phthalate, 0.2% acetylated tributyl citrate, and 0.2% zinc stearate. First, place PBAT and PLA resin in an oven at 90°C for 4 hours for drying. Add the above components to a high-speed mixer and mix at 600rpm / min for 5 minutes, then add them to a twin-screw extruder for extrusion. The barrel temperature of the extruder is 155°C. The extruded material is cooled in the water tank of the extruder and pelletized to obtain the PBAT alloy;

[0066] (4) Preparation of PBAT film: The prepared PBAT alloy was added into a single screw extruder for extrusion blown film at an extrusion temperature of 155° C. to obtain a PBAT film.

[0067] Comparative Example

[0068] Comparative Example 1:

[0069] (1) Using commercially available ordinary corn starch as raw material without any modification;

[0070] (2) Preparation of PBAT alloy: The components of PBAT alloy are: 74.4% PBAT resin, 10% PLA resin, 15% starch, 0.3% acetylated tributyl citrate, and 0.3% erucamide. First, place PBAT and PLA resin in an oven at 90°C for 4 hours for drying. Add the above components to a high-speed mixer and mix at 600 rpm / min for 5 minutes, then add them to a twin-screw extruder for extrusion. The extruder barrel temperature is 155°C. The extruded material is cooled in the extruder water tank and pelletized to obtain the PBAT alloy;

[0071] (4) Preparation of PBAT film: The prepared PBAT alloy was added into a single screw extruder for extrusion blown film at an extrusion temperature of 155° C. to obtain a PBAT film.

[0072] Comparative Example 2:

[0073] (1) Using commercially available ordinary corn starch as raw material without any modification;

[0074] (2) Preparation of PBAT alloy: The components of PBAT alloy are: 69.4% PBAT resin, 10% PLA resin, 20% starch, 0.2% dibutyl phthalate, 0.2% diisooctyl phthalate, and 0.2% zinc stearate. First, place PBAT and PLA resin in an oven at 90°C for 4 hours for drying. Add the above components to a high-speed mixer and mix at 600 rpm / min for 5 minutes, then add them to a twin-screw extruder for extrusion. The extruder barrel temperature is 155°C. The extruded material is cooled in the extruder water tank and pelletized to obtain the PBAT alloy;

[0075] (3) Preparation of PBAT film: The prepared PBAT alloy was added into a single screw extruder for extrusion blowing at an extrusion temperature of 155° C. to obtain a PBAT film.

[0076] The PBAT films prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 were placed in a constant temperature and humidity room at 23±2°C and 50±10%RH for 24 hours of equilibrium treatment. The tensile strength, elongation at break and puncture force performance of the PBAT films were measured using a universal testing machine. The test results are shown in Table 3.

[0077] Table 3: Performance test results of products of Examples 1-3 and Comparative Examples 1-2

[0078]

[0079] It can be seen from the test results in Table 3 that the tensile strength, especially the puncture resistance, of the PBAT film prepared using the modified starch in Examples 1-3 is significantly improved compared with Comparative Examples 1 and 2, indicating that the tensile strength and puncture resistance of the starch-based biodegradable PBAT film can be effectively improved by modifying the starch with a nadic anhydride glyceride solution to prepare the PBAT film.

[0080] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A starch-based biodegradable PBAT film is prepared from the following components in percentage by weight: PBAT resin 50-80%, preferably 55-75%, PLA resin 5%-20%, preferably 5-15%, Modified starch 10%-30%, preferably 15-30%, Plasticizer 0%-2%, preferably 0.02%-1%, Lubricant 0%-2%, preferably 0.02%-1%.

2. The PBAT film according to claim 1, wherein: The PBAT resin is a low melt index resin, and the melt index at 190° C. and 2.16 kg is preferably 3-5 g / 10 min.

3. The PBAT film according to claim 1, wherein: The PLA resin has a melt index of 4-10 g / 10 min at 190° C. and 2.16 kg.

4. The PBAT film according to claim 1, wherein: The modified starch preparation method comprises the following steps: (1) adding nadic anhydride, glycerol, and tetrabutyl titanate into a reaction kettle, slowly heating up, introducing nitrogen gas at the same time, stirring and reacting under normal pressure, and cooling to room temperature in a nitrogen atmosphere to obtain a nadic anhydride glyceride solution; (2) The starch and the nadic anhydride glyceride solution are uniformly mixed, an acidic compound is added, the mixture is heated for reaction, and the mixture is washed with water and then cooled and dried to obtain the nadic anhydride glyceride modified starch.

5. The PBAT film according to claim 4, wherein: In step (1), the amount of glycerol added is 100%-130% by weight of the nadic anhydride, preferably 100%-120%; The addition amount of tetrabutyl titanate is 0.1%-2% of the weight of nadic anhydride.

6. The PBAT film according to claim 4, wherein: In step (2), the starch is a combination of one or more of corn starch, potato starch, and sweet potato starch; Preferably, the amount of nadic anhydride glyceride solution added is 2%-15% of the weight of the starch.

7. The PBAT film according to claim 4, wherein: In step (2), the acidic compound is a combination of one or more of hydrochloric acid, carbonic acid, peracetic acid, and ammonium sulfate, preferably a combination of one or more of hydrochloric acid, carbonic acid, and peracetic acid; Preferably, the amount of the acidic compound added is 1%-6% of the total weight of the starch and nadic anhydride glyceride solution.

8. The PBAT film according to claim 1, wherein: The plasticizer is one or more of tetrabutyl titanate, acetylated tributyl citrate, diisooctyl phthalate and dibutyl phthalate.

9. The PBAT film according to claim 1, wherein: The lubricant is one or more of erucamide, oleamide and zinc stearate.

10. The method for preparing the PBAT film according to any one of claims 1 to 9, comprising the following steps: Evenly mixing PBAT resin, PLA resin, modified starch, optional plasticizer, and optional lubricant to obtain a mixed material; Then the mixture is melt-extruded through a twin-screw extruder, cooled and granulated to obtain a starch-based biodegradable PBAT modified material. Preferably, the barrel temperature of the twin-screw extruder is 50-160° C.; The PBAT modified material is added to a single screw film blowing machine to blow film to obtain a modified PBAT film; preferably, the temperature of the single screw film blowing machine is 100-160°C.

Citation Information

Patent Citations

  • Green biodegradable plastic film and processing technology thereof

    CN109929228A

  • Biodegradable plastic film and preparation method thereof

    CN113754992A

  • Starch modified PBAT / PLA biodegradable plastic film and preparation method thereof

    CN113861635A

  • Completely biodegradable film and preparation method thereof

    CN117050482A

  • Low cost bio-based full degradable film and preparation method thereof

    US20200291225A1